2003
DOI: 10.1021/ie030201m
|View full text |Cite
|
Sign up to set email alerts
|

Drop Size Evolution during the Phase Separation of Liquid Mixtures

Abstract: After quenching a partially miscible, initially homogeneous, critical liquid mixture to a temperature T deeply below its critical point of miscibility, we observed the formation of rapidly coalescing droplets, whose size grows linearly with time, thus indicating that the phase separation process is driven by convection. Eventually, when their size reaches a critical length, which is roughly equal to one-tenth of the capillary length, the nucleating drops start sedimenting and the two phases rapidly segregate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Then, as soon as the nuclei reach a limit size of about 1 mm, which is approximately one-tenth the capillary length in the experiments by Califano and Mauri (2004) , they rapidly sediment, leading to an equilibrium state with two coexisting phases, within a time of about 10 s, in agreement with experimental observations ( Califano and Mauri, 2004;Califano et al, 2005 ).…”
Section: Mixing and Demixingsupporting
confidence: 86%
See 1 more Smart Citation
“…Then, as soon as the nuclei reach a limit size of about 1 mm, which is approximately one-tenth the capillary length in the experiments by Califano and Mauri (2004) , they rapidly sediment, leading to an equilibrium state with two coexisting phases, within a time of about 10 s, in agreement with experimental observations ( Califano and Mauri, 2004;Califano et al, 2005 ).…”
Section: Mixing and Demixingsupporting
confidence: 86%
“…As shown by Santonicola et al (2001) , this process is very slow, as after one hour the interfacial region is only a few millimeters thick. On the other hand, when the mixture is quenched back to 20 °C, the ensuing phase separation process is very rapid and a two-phase equilibrium state is reached within a few seconds ( Califano and Mauri, 2004;Califano et al, 2005 ). To explain this behavior, let us describe first the mixing process, assuming that the mixture is initially quiescent and phase separated (with > 2) along a flat interface at z = 0 , and is then instantaneously heated, so that < 2 at all times t ≥ 0.…”
Section: Mixing and Demixingmentioning
confidence: 99%
“…In previous works we have shown that, for a low-viscosity binary system in a uniform temperature field, this process is driven by the convection induced by phase transition, which is responsible for the enhanced coalescence between single-phase microdomains. [1][2][3][4][5][6] When the temperature field is inhomogeneous, however, another effect becomes relevant, namely, convective heat transport due to phase transition. This effect is well known in vapor-liquid phase transitions, where the density mismatch between the component phases drives a strong, turbulent convection which enhances heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5,6,17 Experimentally, when a nearly isopycnic, low-viscosity binary mixture is quenched deeply and rapidly into the spinodal region of its phase diagram in the presence of a temperature gradient, it develops a unidirectional and large-scale motion of the nucleating droplets along the direction of the temperature gradient 3,14 which, even in the absence of buoyancy, is responsible for a rapid and complete segregation of the mixture. This was initially observed by Califano and Mauri, 3 who used a nearly isopycnic hexadecane-acetone mixture in a temperature-regulated cell for investigating drop size evolution in a phaseseparating system.…”
Section: Introductionmentioning
confidence: 99%
“…with Ψ = 2.1. We chose this particular value of Ψ because Vol.79 (2011) that is the Margules parameter of the water-acetonitrile-toluene mixture at 20 • C that we used in our own experimental work [17,18,53,7,46]. The first row of images represents the results for N P e = 0, i.e.…”
Section: Vol79 (2011)mentioning
confidence: 99%